ANALISIS DAMPAK INDEKS PEMBANGUNAN MANUSIA(IPM) TERHADAP TINGKAT KEMISKINAN DI PROVINSI SUMATERA UTARA (2017-2022) - Febrianti, Nisa; Br Pulungan, Salsabila; Azarita Br Ginting, Ruhiya; Mutia, Sarah; Dwi Adelia, Tamara (PT. ANAN PUBLISHER CENDEKIA, 2024)
Poverty is a complex economic issue that involves multiple dimensions. Therefore, efforts are needed to find solutions to overcome or at least reduce the level of poverty. The objective of this research is to analyze the impact of the economic growth rate on the poverty level in the North Sumatra Province. The author employs research instruments such as literature reviews, documentation studies, and internet searches. The data are sourced from secondary data obtained from relevant agencies, especially the Central Statistics Agency (Badan Pusat Statistik) of North Sumatra, covering the period from 2017 to 2022. In analyzing the data, the author utilizes the technique of simple linear regression analysis. The results of data processing indicate that the Human Development Index (HDI) from 2017 to 2022 has an impact on the poverty level in North Sumatra from 2017 to 2022.